ChemInform Abstract: Discovery and Total Synthesis of Streptoaminals: Antimicrobial [5, 5]‐Spirohemiaminals from the Combined‐Culture of Streptomyces nigrescens and Tsukamurella pulmonis. Issue 52 (6th December 2016) - Sugiyama, Ryosuke; Nishimura, Shinichi; Ozaki, Taro; Asamizu, Shumpei; Onaka, Hiroyasu; Kakeya, Hideaki
Abstract: Streptoaminal‐9n (I) and its enantiomer (II) show antibacterial activity.